The Effectiveness of The Video Critic Method in Multiple Intelligences-Based Learning for VIII Class Students at Madrasah Tsanawiyah - Sutipyo Ru'iya; Yusron Masduki; Amrih Latifah (Jurnal Inspirasi Pendidikan, 2022)
Strategy is important in the learning process to encourage student success. The teacher's expertise in compiling and using appropriate-strategies with learning materials will increase the effectiveness of learning. This study is a pre-experimental design study, intending to know the effectiveness of the video critic method in multiple intelligences-based-learning in class VIII students at Madrasah Tsanawiyah. The sample used was 30 students that choosen by random sampling. The data collection instrument was a cognitive test. The data analysis technique used a different test "t" test with the help of the Statistical Package for the Social Sciences (SPSS) 21. The results showed learning-outcomes incrased before and after using the video critic method based on multiple intelligences research (MIR). The results of the "t" difference test obtained a value of 10,806 (p < .00), so it can be concluded that there is a significant difference between the learning outcomes before using the MIR-based video critic method and the learning outcomes after using the MIR-based video critic method. This happens because students can learn according to their learning style, so they enjoy learning and learning more meaningfully.